Revive your heart putting life in perspective - Khan, Nouman Ali (Kube Publishing Ltd, 2017)
Revive Your Heart is a call for spiritual renewal and an invitation to have a conversation with one of the world's most recognizable voices on Islam, Nouman Ali Khan. This collection of essays is disarmingly simple, yet it challenges us to change. To revise our actions, our assumptions and our beliefs so we can be transformed from within, as well as externally. It aims to help modern Muslims maintain a spiritual connection with Allah and to address the challenges facing believers today: the disunity in the Muslim community, terrorists acting in the name of Islam, and the disconnection with Allah. These challenges and more are tackled by Nouman Ali Khan, with his profound engagement with the Qur'an, in his trademark voice that is sought out by millions of Muslims on a daily basis.